OSTEOARTHRITIS AND GERIATRIC SYNDROMES: FEATURES OF THE RELATIONSHIP AND MANAGEMENT OPPORTUNITIES (LITERATURE REVIEW) - Iniushyna, Alina; Zaverukha, Nataliia; Grygorieva, Nataliia; Protsiuk, Olha (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2025)
Osteoarthritis (OA) is one of the leading age-associated musculoskeletal isorders, the prevalence of which is increasing due to population aging. The aim of this study is to analyze current literature data regarding the relation and management possibilities of OA and common geriatric syndromes. Methods. A systematic literature review was conducted using analytical methods across scientific databases such as PubMed, Web of Science, Scopus, and Google Scholar for the period 2019–2024. The search was performed using the keywords: “osteoarthritis,” “sarcopenia,” “sarcopenic obesity,” “dysmobility,” “malnutrition,” and “undernutrition.” Results. Typical geriatric syndromes (sarcopenia, sarcopenic obesity, dysmobility syndrome, and malnutrition) are the common phenomenons among OA patients. These conditions share common pathophysiological mechanisms that mutually aggravate each other’s course. The analysis of current literature revealed a lack of comprehensive studies on the combination of OA with geriatric syndromes, especially in the Ukrainian scientific space. This article provides an overview and analysis of current scientific data regarding prevalence, risk factors, pathophysiological mechanisms, diagnostic features, clinical manifestations, as well as potential approaches to treatment, prevention, and rehabilitation of patients with OA in combination with the most common geriatric syndromes. Conclusions. The literature analysis demonstrated bidirectional interaction mechanisms between OA and other geriatric syndromes, highlighting the importance of developing effective strategies for early detection, prevention, and management of such patients within a multidisciplinary approach.